ANALISIS RASIO PERDAGANGAN EKSPOR IMPOR INDONESIA DAN THAILAND PERIODE 2019-2021 - R. Reddya Fanada Wibisana; Dhea Zalfa Artamevia; Khalda Afifah Garyalisni; Siti Innaya Rahmani Sitepu (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Trade is one of the most influential aspects of a country's economy. Trading activities carried out by a country, both exports and imports, provide an explanation of trade transactions within the country itself. Indonesia is a country with an active flow of trade transactions with several fellow Southeast Asian countries, especially Thailand. The purpose of this study was to determine the development of export and import values between Indonesia and Thailand through the parameters of the results of the export import trade between the two countries. The method used in collecting data for thisstudy uses secondary data taken from the Badan Pusat Statistik. Data analysis techniques use descriptive data analysis and by observing export and import values,Trade balance, and traderatios. The results obtained show thattrade between Indonesia and Thailand is dominated by imports